Optimasi Proses Hidrolisis Vinasse Sebagai Bahan Baku Resin Polimer yang Ramah Lingkungan - Lestari Hetalesi Saputri (Universitas Ahmad Dahlan, 2016)
Vinasse contains some amine, carboxyl and hydroxyl groups in it’s organic acids. These groups when being combined with other materials can be synthesized into a raw material of coating material. This research aims to break vinasse chain by hydrolysis into amino acids. Hydrolysis is carried out at 110 °C with a residence time of 60-150 minutes (with 30-minute intervals). In addition, the comparison between the volume of vinasse and HCl is 1: 1, 1: 2, 1: 3 and 1: 4. Then the material from the hydrolysis are analyzed their groups. Quantitative analysis is required to determine the composition of vinasse that will be added in the next polimerization processing. The result showed that the optimum conditions of hydrolysis process is at 2 hours and volume HCl with the ratio of 1: 3. FTIR analysis indicated the presence of carboxyl and amines groups on hydrolyzate. The long term goal of this research is the use of vinasse as a coating material derived from biomaterials, as well as renewable materials. It could be expected that hydrolysis under acidic conditions can be an initial step to a coating material with vinasse as a raw material base. Keywords: Vinasse, Polimer Resin, Hydrolysis, Coating Material.